The Relationship Between Esg And The Profitability Of Companies Listed On The IDX - Nugraha, Ihza Abdhilla; Paramu, Hadi; Utami, Elok Sri (Universitas Muhammadiyah Pontianak, 2026)
This study investigates the relationship between Environmental, Social, and Governance (ESG) practices and profitability among companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Using Return on Assets (ROA), Return on Equity (ROE), and Earnings per Share (EPS) as profitability indicators, data from 56 purposively selected companies were analyzed with Pearson correlation. Results indicate that the social aspect and overall ESG score are significantly related to all profitability indicators, while environmental and governance dimensions significantly relate only to EPS. These findings suggest ESG, particularly social and integrated implementation, contributes to profitability and sustainable corporate performance.